Impact of urgently initiated tele-prescription due to COVID-19 on glycemic control in patients with type 2 diabetes - Sung-Don Park; Na-young Kim; Jae-Han Jeon; Jung-Guk Kim; In-Kyu Lee; Keun-Gyu Park; Yeon-Kyung Choi (The Korean Journal of Internal Medicine, 2021)
Background/Aims Coronavirus disease 2019 (COVID-19) is a global pandemic that had affected more than 13,000 people in South Korea by July 2020. To prevent spread of COVID-19, tele-prescription was permitted temporarily. This study investigated the impact of tele-prescription on glycemic control in patients with type 2 diabetes. Methods Glycated hemoglobin (HbA1c) concentrations were retrospectively analyzed in patients with type 2 diabetes who were treated with tele-prescription because of COVID-19 and those who were treated by face-to-face care (non-tele-prescription group) enrolled at the same period of time. Mean HbA1c concentrations and mean change in HbA1c concentration (ΔHbA1c) were compared in these two groups. Results The mean HbA1c levels of patients were significantly higher after than before the tele-prescription period (7.46% ± 1.24% vs. 7.27% ± 1.13%, p < 0.05). Mean ΔHbA1c was significantly higher in the tele-prescription than in the non-tele-prescription group (0.19% ± 0.68% vs. 0.04% ± 0.95%, p < 0.05). HbA1c was significantly greater in patients taking fewer oral hypoglycemic agents, no insulin, fewer comorbidities (e.g., coronary artery disease, cerebrovascular accident, and diabetic neuropathy), and higher baseline HbA1c. Conclusions Tele-prescription may worsen glycemic control in patients with type 2 diabetes during public health crises.